1925
DOI: 10.1002/zaac.19251430117
|View full text |Cite
|
Sign up to set email alerts
|

Zur Deutung der Kaltbearbeitung auf Grund elektrischer Messungen. II

Abstract: Auf diese Anslogie haben such G. MA~ING und M. POLANPI hingewiesen, wenigstens soweit sie den Temperaturkoeffizienten betrifft. (Ergebniese der exakten Naturw. Z (1923), 177.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1925
1925
1953
1953

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…During recent work in this laboratory (Broom 1952) on the resistivity of cold-drawn wires, some results were found which suggested deviations from the rule. The most recent systematic work on the validity of the rule for a metal in various states of deformation is that by Geiss :and van Liempt (1925, 1927 who found that, for tungsten, molybdenum, platinum, and nickel, deformation produced variations in the product of up to 2 per cent. They give no indication of their experimental error but conclude that the rule is true.…”
Section: Introductionmentioning
confidence: 99%
“…During recent work in this laboratory (Broom 1952) on the resistivity of cold-drawn wires, some results were found which suggested deviations from the rule. The most recent systematic work on the validity of the rule for a metal in various states of deformation is that by Geiss :and van Liempt (1925, 1927 who found that, for tungsten, molybdenum, platinum, and nickel, deformation produced variations in the product of up to 2 per cent. They give no indication of their experimental error but conclude that the rule is true.…”
Section: Introductionmentioning
confidence: 99%